Analisis kemampuan membaca pemahaman peserta didik kelas v pada pembelajaran bahasa indonesia kurikulum merdeka - Zalsabilla Sekar Fiqhanna Aranti; Siti Istiyati; Fadhil Purnama Adi (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2024)
The aim of this research is to describe the reading comprehension abilities, barriers, and efforts to overcome barriers to reading comprehension of class V students at SDN Cinderejo Surakarta. This research approach is descriptive qualitative. The data collection techniques for this research are interviews, tests and observations. The data validity technique in this research is triangulation of sources and techniques. This research uses the Miles and Hubberman model data analysis technique. The results of the research show that students' reading comprehension abilities are at a literal level of 31.57%, at an interpretive understanding level of 28.42%, at a critical level of 28.07%, and at a creative level of 47.3%. Students who cannot understand reading at a literal level will find it difficult to understand reading at an interpretive level, and so on. Barriers to reading comprehension experienced by students are poor physical condition, low student motivation, and a home environment that does not support students in reading comprehension. The efforts made are learning while playing, providing verbal motivation to students, providing a comfortable reading room, getting students used to reading, and collaborating with students' parents. The conclusion of this research is that students' overall reading comprehension ability is included in the poor category, so it is necessary to try to overcome barriers to students' reading comprehension.